Latin America and the Caribbean Poverty and Labor Brief, June 2013 : Shifting Gears to Accelerate Shared Prosperity in Latin America and the Caribbean - World Bank (Washington, DC, 2013)
The Latin America and Caribbean (LAC) region has made laudable progress in the past fifteen years in reducing poverty, building the middle class, and promoting prosperity for all levels of society. Extreme poverty, defined in this region as life on less than $2.50 a day, has declined by half, while in 2011 for the first time in recorded history the LAC region had a larger number of people in the middle class than in poverty. Across this region of close to 600 million people, the poor have been gaining faster than the already well off. But despite these impressive achievements, about 80 million people still live in extreme poverty, half of them in Brazil and Mexico. And millions more who have risen out of poverty risk being pulled back down into it by economic shocks and severe weather brought on by climate change. This brief reviews the LAC's progress toward these objectives, outlines the continuing challenges and proposes a policy framework for keeping the region on its upward arc and picking up the speed.